Design of a high‐gain omni directional microstrip dipole array with low side lobe level in the elevation plane. Issue 3 (5th February 2018) - Darvazehban, Amin; Khaledian, Seiran; Manoochehri, Omid; Salari, Mohammad Ali
Abstract: A novel low‐cost high‐gain antenna array with omnidirectional radiation pattern for applications in X‐band (8.5–11.5 GHz) is proposed. A maximum gain of 13.6 dB and a side lobe level of −18 dB in the elevation plane have been achieved using an array consisting of 16 microstrip dipole antennas. Synthesis of Chebyshev amplitude distribution was done by using constant attenuators. This system is specifically useful for point‐to‐ multipoint communications and direction finding systems. The whole system was fabricated and simulation results are in good agreement with the measurements.